Child abuse in Malaysia contributing factors and solutions from Quránic perspective - Fatah Yasin, Raudlotul Firdaus; Hazwani, Hamdzah (IIUM Press, International Islamic University Malaysia, 2017)
Children are an integral asset for future development of a nation. In lieu of this notion, almost all countries pay considerable attention to their development and well-being. In recent times, child abuse has become a worrying phenomenon that can no longer be ignored. This issue is constantly making headlines in national newspapers in Malaysia. The statistics issued by the Department of Social Welfare Malaysia indicate that the number of child abuse cases reported is increasing dramatically from 2008 until 2013. In 2008, 2300 children were reported to be abused, and the figure has increased to 44.1% in 2013 when 4119 children were reported to have been abused by either their own parents or guardians. In Islam, children are a monumental trust from Allah SWT, since Allah SWT has mandated parents the responsibility to raise and educate children. Treating them well is thus a personal and religious obligation. Conversely, child abuse is indeed a great sin. Hence, this study seeks to investigate an overview of child abuse in Malaysia and how Islam prohibits child abuse by exploring existing research works, articles, journals, theses and books from library and archive. Analysis of Qur’anic verses and interpretation related to the prohibition of child abuse, as well as the kind treatment of Prophet Muhammad SAW and his companions towards the children and the youth, is also carried out, which serves as evidence of child abuse prevention in modern times in Malaysia. The solutions proposed by this study are mainly divided into three stages: (i) the establishment of individual awareness, (ii) the establishment of social awareness and (iii) institutional reform.